Special Group Discussion: nutrition and Covid-19 comparison in several countries - Luciana B Sutanto (Indonesian Nutrition Association, 2022)
Patients with COVID-19 who are in the ICU considered to be extremely high malnutrition, which is caused by food intake matter and the disease itself. In critically ill, the definition of malnutrition is not only based on weight loss but also muscle wasting, sarcopenia and metabolic dysregulation. Good nutrition management prevents malnutrition getting worse. Nutritional theraphy is an essential element of the patients management. Nutritional screening and assessment, as well as nutritional management, should be integrated into general therapeutic strategy. Nutrition theraphy to ICU patients with COVID-19 has been published by some institutions/organizations.